COLD-PCR and microarray: two independent highly sensitive approaches allowing the identification of fetal paternally inherited mutations in maternal plasma. Issue 7 (24th February 2016) - Galbiati, Silvia; Monguzzi, Alessandra; Damin, Francesco; Soriani, Nadia; Passiu, Marianna; Castellani, Carlo; Natacci, Federica; Curcio, Cristina; Seia, Manuela; Lalatta, Faustina; Chiari, Marcella; Ferrari, Maurizio; et al.
Abstract : Background: Until now, non-invasive prenatal diagnosis of genetic diseases found only limited routine applications. In autosomal recessive diseases, it can be used to determine the carrier status of the fetus through the detection of a paternally inherited disease allele in cases where maternal and paternal mutated alleles differ. Methods: Conditions for non-invasive identification of fetal paternally inherited mutations in maternal plasma were developed by two independent approaches: coamplification at lower denaturation temperature-PCR (COLD-PCR) and highly sensitive microarrays. Assays were designed for identifying 14 mutations, 7 causing β-thalassaemia and 7 cystic fibrosis. Results: In total, 87 non-invasive prenatal diagnoses were performed by COLD-PCR in 75 couples at risk for β-thalassaemia and 12 for cystic fibrosis. First, to identify the more appropriate methodology for the analysis of minority mutated fetal alleles in maternal plasma, both fast and full COLD-PCR protocols were developed for the most common Italian β-thalassaemia Cd39 and IVSI.110 mutations. In 5 out of 31 samples, no enrichment was obtained with the fast protocol, while full COLD-PCR provided the correct fetal genotypes. Thus, full COLD-PCR protocols were developed for all the remaining mutations and all analyses confirmed the fetal genotypes obtained by invasive prenatal diagnosis. Microarray analysis was performed on 40 samples from 28 couples at risk for β-thalassaemia and 12 for cystic fibrosis. Results were in complete concordance with those obtained by both COLD-PCR and invasive procedures. Conclusions: COLD-PCR and microarray approaches are not expensive, simple to handle, fast and can be easily set up in specialised clinical laboratories where prenatal diagnosis is routinely performed.